Grain growth and segregation in Fe-doped SrTiO3: Experimental evidence for solute drag. Issue 4 (April 2023) - Zahler, M. Pascal; Kraschewski, Simon M.; Störmer, Heike; Gerthsen, Dagmar; Bäurer, Michael; Rheinheimer, Wolfgang
Abstract: In functional ceramics, the impact of dopants on bulk crystals is generally well understood. Their impact on grain boundaries is less well known. The present study investigates the impact of acceptor dopants on grain growth in strontium titanate. Scanning electron microscopy and analytical (scanning) transmission electron microscopy have been used to gain knowledge on Fe segregation behavior, grain sizes, and grain size distributions of SrTiO3 . While undoped microstructures show normal grain growth at low temperatures (<1350 °C), doped microstructures evolve bimodally. With increasing acceptor dopant concentration, an increasing population of small grains develops. It is shown that Fe segregates to the grain boundaries due to its negative charge and a positive boundary potential. Thus, the experimental findings seem to be well explained by the theory of solute drag: The diffusion of segregated defects ('solutes') at grain boundaries can retard grain boundary migration.